2007
DOI: 10.1109/iembs.2007.4353825
|View full text |Cite
|
Sign up to set email alerts
|

How stiff and thin can an engineered extracellular matrix be? Modeling molecular forces at the cell-matrix interface

Abstract: The function of tissue cells can be significantly modulated by changes in the local mechanical environment, including the stiffness of the substrata to which these cells adhere. To engineer surfaces that maintain or induce cell functions, it is important to understand the force, length, and timescales over which cell surface receptors probe the local mechanical environment. Here we show how simplified continuum and atomistic simulations of the nanoscale forces between cell surface receptors and extracellular m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…This gradual masking of mechanoselective adhesion is consistent with previous studies on eukaryotic cells but is observed here after addition of just a single compliant polyelectrolyte layer; decreased adhesion of fibroblasts is not observed until addition of at least five bilayers of the compliant PEM to the stiff PEM. This may be attributed in part to the increased forces and distances over which eukaryotic cells can strain the underlying substrata through actomyosin traction at focal adhesions of diameters comparable to a single bacterium. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This gradual masking of mechanoselective adhesion is consistent with previous studies on eukaryotic cells but is observed here after addition of just a single compliant polyelectrolyte layer; decreased adhesion of fibroblasts is not observed until addition of at least five bilayers of the compliant PEM to the stiff PEM. This may be attributed in part to the increased forces and distances over which eukaryotic cells can strain the underlying substrata through actomyosin traction at focal adhesions of diameters comparable to a single bacterium. , …”
Section: Resultsmentioning
confidence: 99%
“…This may be attributed in part to the increased forces and distances over which eukaryotic cells can strain the underlying substrata through actomyosin traction at focal adhesions of diameters comparable to a single bacterium. 53,54 3.5. Mechanoselective Adhesion is Independent of Monovalent Ion Concentration.…”
Section: S Epidermidis Adhesion Modulatedmentioning
confidence: 99%
“…Accordingly, it is becoming increasingly clear that the development of functional in vitro models of tissue patho/physiology depends on the ability to understand, predict, and harness the chemical and mechanical properties of extracellular substrata [1,2]. Several descriptive studies have highlighted the cooperative effects of ligand presentation and substrata stiffness on cellular functions ranging from adhesion and motility to morphogenesis and remodeling [3,4]; furthermore, these findings have led to the development of new synthetic substrata offering improved control over independent biochemical and mechanical cues [5-12]. In particular, poly (acrylamide) (PA) hydrogels of approximate elastic modulus ( E ) of 10 1 –10 5 Pa have been surface-functionalized with adhesion proteins or ligands, and used extensively to study chemo-mechanical effects on a variety of cell fate processes including fibroblast migration and contractility [5], endothelial cell adhesion [6,7], myotube formation [8], stem cell differentiation [9], and hepatocyte spreading [10].…”
Section: Introductionmentioning
confidence: 99%
“…Polyethylene glycol (PEG)-based substrata exhibiting similar E comparable to those of PA hydrogels have also been used to evaluate the effects of mechanical compliance on cellular morphology and phenotype [11]. However, because changes in composition or extent of crosslinking in natural and aforementioned synthetic systems may also affect surface ligand density, configurations, and distensibility [12], the interplay between biochemical and mechanical cues on cellular fates has not yet been fully decoupled. A system amenable to independent modulation of chemical composition, stiffness, and ligand presentation has the potential to help elucidate the mechanisms of cooperative chemomechanical feedback, as well as aid in the development of highly functional in vitro models of tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the studies on cell functions during the tissue-specific homing process indicate that mechanical properties of the surrounding microenvironment are critical for regulating cell-ECM interactions. [113][114][115] Relevant cell-based assays can be carried out on plates coated for example, with ECM-derived integrin ligands. 116 Thus, the experimental models implementing cell exposure to molecules adsorbed on substrates enabled to demonstrate that collagens, laminins, 'RGD'-containing proteins (fibronectin, fibrin, vitronectin) as well as immunoglobulin superfamily proteins (VCAM, ICAMs) are capable of mediating cell adhesion.…”
Section: Using Chemotaxis Systems To Elucidate the Underlying Biologymentioning
confidence: 99%